Lineamientos para la gestión de riesgo en las estaciones de servicios de gasolina en Bogotá (2020)
The service stations are ruled by operation and construction licenses, which are inspected to monitor the risks inherent to these stations, for this purpose the obligations according to 1073 decree of 2015 were identified and related regarding to social, economic and ambiental ambit which helped to identified the correct function of an service stations. Subsequently, the activities of each operation were related to the obligations that they must fulfill in order to determine the possible risks to which they are subjected to, after that, they were analyzed and evaluated by using an Ecopetrol RAM matrix. This risk assessment begins with the identification of the level of probability, and then request a semi-qualitative assessment defining the level of threat. The highest rated risks were: soil contamination, alteration of the natural environment and customer dissatisfaction. For that, the following mitigation strategies were defined for each of these three risks: contingency plans, environmental monitoring and audits.